What do you think it means? Using cognitive interviewing to improve measurement in implementation science: description and case example - Zabin Patel-Syed; Sara Becker; Miranda Olson; Hailey Rinella; Kelli Scott (Implementation Science Communications, 2024)
Abstract Pragmatic measures are essential to evaluate the implementation of evidence-based interventions. Cognitive interviewing, a qualitative method that collects partner feedback throughout measure development, is particularly useful for developing pragmatic implementation measures. Measure developers can use cognitive interviewing to increase a measure’s fit within a particular implementation context. However, cognitive interviewing is underused in implementation research, where most measures remain “homegrown” and used for single studies. We provide a rationale for using cognitive interviewing in implementation science studies and illustrate its use through a case example employing cognitive interviewing to inform development of a measurement-based care protocol for implementation in opioid treatment programs. Applications of cognitive interviewing, including developing a common language with partners and collecting multi-level feedback on assessment procedures, to improve measurement in implementation science are discussed.